2024
DOI: 10.3390/polym16020168
|View full text |Cite
|
Sign up to set email alerts
|

Birefringence in Injection-Molded Cyclic Olefin Copolymer Substrates and Its Impact on Integrated Photonic Structures

Stefan Kefer,
Tobias Limbach,
Natalie Pape
et al.

Abstract: This contribution quantifies the birefringence within injection-molded cyclic olefin copolymer plates and discusses its impact on the mechanical properties of the plates. It also focuses on the impact of birefringence on integrated waveguides and Bragg gratings and provides fabrication guidelines for such structures. The anisotropy in all three dimensions of the workpiece is examined by means of polarimetry and a prism coupler. It is found that the birefringence is inhomogenously distributed within the workpie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For example, various investigations have shown that the transmission behavior of waveguides is strongly dependent on the polymer orientation. The sensor signals from Bragg gratings written into waveguides are also direction-dependent [38]. Understanding optical anisotropy in injection-molded polmyer substrates can significantly impact the functionality of integrated optical elements.…”
Section: Resultsmentioning
confidence: 99%
“…For example, various investigations have shown that the transmission behavior of waveguides is strongly dependent on the polymer orientation. The sensor signals from Bragg gratings written into waveguides are also direction-dependent [38]. Understanding optical anisotropy in injection-molded polmyer substrates can significantly impact the functionality of integrated optical elements.…”
Section: Resultsmentioning
confidence: 99%